Analysis and Design of Information Systems Sales Separepart Gemilang Jaya Motor - Waskito, Eko (APMMI - Asosiasi Profesi Multimedia Indonesia, 2010)
The development of increasingly advanced technology it will affect the switching system that is still simple to use computerized systems. With the migration using the computerized system is expected to facilitate admins in data processing. The existence of computerized information systems affect various aspects, including business and sales are usually the manual accounting system that is generally make books only. Thus a system is created for the sale and purchase of information systems using computer programs more effective. Work practices aim to apply a science that has been obtained to be able to analyze and design and create an information system. Here practice doing practical work at the Gemilang Jaya Motor to create one system of selling and purchasing information. Sales and purchase information system uses a desktop-based computer system that is using the program Microsoft Visual Basic 6.0 application and its data processing using Microsoft Office Access 2007. With this information system is expected to help the admin in the process of transaction data processing is more accurate. Â Keywords: sales and purchases, Information Systems